Endoscopic, “Scarless” Composite Flap Face and Neck Lift - Mani, Marc (Facial Plastic Surgery, 2023)
Deep-plane or composite flap facelift techniques allow deep structural rejuvenation of the face by release of retaining ligaments in the subsuperficial musculoaponeurotic system (sub-SMAS) plane with elevation and fixation of the SMAS/platysma/skin flap as a single, “en bloc” unit. This means that in the cases with mild to moderate skin laxity, the preauricular incision serves the purpose of access only. The author therefore developed an endoscopic-assisted, en bloc composite flap face and neck lift without a preauricular incision. The technique uses the prezygomatic and premasseteric (facial) and subplatysmal (neck) spaces as ideal optical cavities for endoscopic dissection and ligament release. Verticalization of fixation vectors and modified concho-mastoid traction sutures are used to minimize preauricular skin redundancy. The surgical procedure is described in detail. Clinical experience in 41 consecutive cases and comparison to other techniques with respect to relevant anatomy are also presented. This endoscopic en bloc composite flap facelift technique consistently and safely produced results comparable to conventional, “open” composite flap facelifts done by the same surgeon on similar candidates during a prior period.
Keywords: deep plane; composite flap; facelift; endoscopic facelift